Advanced LC-MS applications in metabolomics - Han, Jun (Metabolomics scientist); Parker, Carol (Researcher in proteomics); Borchers, Christoph (Professor of Biochemistry) (Future science., 2015)
Genomes, both healthy and diseased, can now be quickly sequenced. Systems-level approaches are needed to fully understand the implications, including proteomics. The metabolome is highly complicated, dynamic and multifaceted. Metabolome analysis heavily relies on mass spectrometry. Developments in instrumentation, sample preparation and computational analysis have furthered proteomics research greatly. This book highlights the advanced instrumentation and methodologies available in LC-MS-based metabolomics. The book then looks at the most novel and exciting applications in metabolomics through a series of case studies.